SOSIALISASI ENERGI TERBARUKAN KEPADA KELOMPOK TANI DI DUSUN BUANI, DESA BENTEK, KECAMATAN GANGGA, KABUPATEN LOMBOK UTARA - Ida Bagus Fery Citarsa; I Ketut Wiryajati; I Nyoman Wahyu Satiawan; I Made Budi Suksmadana; Supriono Supriono; Made Sutha Yadnya; Ida Ayu Sri Adnyani (Jurnal Pepadu, 2026)
Three key elements are needed to utilize renewable energy within a community: technological readiness, human resource readiness, and data on local energy potential. Human resource readiness can be measured based on the community's knowledge of renewable energy. Similarly, farmer groups, as part of the human resource that requires energy for their activities, both at home and in the workplace, need to prepare themselves with knowledge about renewable energy utilization to meet future needs. ‘Remaja Tani Serba Guna Buani’, one of the farmers group in Buani Hamlet, also needs assistance in preparing itself for renewable energy utilization. This is due to the lower-middle educational background of its members and the lack of sosialization to them. Therefore, sosialization on renewable energy is necessary to help them understand the various types of renewable energy and the potential for renewable energy in their area to support sustainable energy conservation. This activity was carried out in three stages: preparation, implementation, and evaluation. The evaluation revealed that 73.69% of participants answered the questions with a score of "fair to excellent," while 26.31% of participants answered the questions with a score of "very poor to poor." This indicates that the sosialization activities provided understanding to the majority of the farmer group members.